Barriers to palliative care in people with chronic obstructive pulmonary disease in home care: A qualitative study of the perspective of professional caregivers. Issue 3 (15th January 2018) - Mousing, Camilla A; Timm, Helle; Lomborg, Kirsten; Kirkevold, Marit
Abstract : Aims and objectives: To examine the experiences with palliative care in people with chronic obstructive pulmonary disease among professional caregivers in a Danish home care setting. Background: Many patients with advanced chronic obstructive pulmonary disease depend on professional caregivers in the primary sector to provide assistance and care. However, chronic obstructive pulmonary disease patients receive no or only very little palliative care compared to patients with cancer although they may have many burdensome symptoms. Design: Qualitative explorative study. Methods: In 2013–2014, ten professional caregivers from three districts in a Danish municipality were followed during home visits to patients with chronic obstructive pulmonary disease and individual interviews about palliative care were subsequently conducted. In 2014, 66 professional caregivers, representing eleven home care districts, participated in ten group discussions about palliative care needs in this group of patients. Data were analysed using qualitative descriptive analysis. Results: The study revealed a nonawareness of palliative care for patients with chronic obstructive pulmonary disease among the professional caregivers who expressed vague understanding of palliative care and lack of knowledge about the disease. Organisational barriers, such as lack of time and continuity in patient care, lack of opportunity to discuss palliative care and lack of peer learning were experienced as challenging in the provision of palliative care. Nonawareness and organisational barriers led to difficulties in identifying palliative care needs and reluctance to initiate conversations about palliative care. Conclusion: The findings indicate a need for education, training and reflection among professional caregivers in home care. Also, organisational changes may be needed to reduce the barriers to palliative care. Relevance to clinical practice: The findings uncovered barriers to palliative care that must be addressed. Targeted educational programmes and organisational changes may increase the ability to identify palliative care needs and initiate and evaluate palliative interventions.